Mexico : Determinants of Learning Policy Note - World Bank (Washington, DC, 2012)
This report aims to identify the determinants of learning in Mexico, focusing on equity, cross-country comparisons and national studies. The present report provides new analytical work on the determinants of learning using international and national assessments, as well as new work on the returns to quality of education and an assessment of media coverage of international assessments. The report is organized as follows: Chapter 1 reviews the existing international and Mexican literature on education quality and the determinants of learning. Chapter 2 presents an overview of the state of education in Mexico. Chapter 3 discusses the analysis of the National Assessments (Estandures Nacionales) from 1998 to 2000 and the results of the analysis of PISA 2000 and PISA 2003 data. Finally, Chapter 4 concludes the main report with an agenda for action, which responds to the education situation in Mexico. The report's main message is that Mexico needs to increase secondary school enrollment rates. The country continues to do well at maintaining equity in terms of the impact of family background on scores and the very low dispersion between top and bottom achievers, which is unusual for a Latin American country participating in international achievement tests. To improve quality, Mexican schools need to improve the school climate and continue efforts to move decision-making from the state level education secretariats to the school level, thus increasing school autonomy. Also, accountability needs to be further strengthened by involving parents and the community more and setting clear goals and clear vision for the school system. Finally, Mexico's remarkable efforts to improve assessment of the system should continue, with continued participation in international achievement tests, as well as improvements of the national assessment system.